Active databases as information systems - Goldin, D.; Srinivasa, S.; Srikanti, V. (Proceedings. International Database Engineering and Applications Symposium, 2004. IDEAS '04, 2004)
Database driven Information Systems (IS) have two distinct integrity concerns: static, or data integrity and dynamic integrity. Static integrity addresses situations within a particular database state, or instance and dynamic integrity is concerned with state sequences instead. Dynamic integrity issues come to the fore when services are designed over the database. Information systems are defined as a collection of services and dynamic integrity is therefore an essential part of IS design. Consequently, designers of information systems have been routinely concerned with dynamic integrity. Active databases (ADBs) that add an element of dynamics into database systems, have mainly addressed static integrity concerns. While there have been some attempts to incorporate dynamic integrity concerns within the framework of ADBs, a general solution is still wanting. This work addresses dynamic integrity concerns in ADBs by changing the perspective of an ADB from a database system augmented with rules to a database driven IS that offers rule-based services. This change in perspective offers a promising approach for addressing ADB shortcomings, and reveals a roadmap of directions for future ADB research.